CLASSIFICATION OF EMOTIONS IN THE LYRICS OF NANCY AJRAM'S SONGS (DAVID KRECH'S PSYCHOLOGICAL ANALYSIS OF LITERATURE) - Arifah, Aminatul; Ismil Hakim, Rani (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Emotions are feelings that have a big influence on behavior. Therefore, emotions are an important aspect in human life. Humans have many ways to express the emotions they feel. For example, literary works include poetry, novels, films, dramas, diaries, biographies and songs. However, it is not uncommon for someone to use a foreign language song to describe their feelings, the lyrics of the song are not in sync with what the person wants to convey because they don't know how to translate the song lyrics, let alone the meaning of the song. . This research aims to find out what emotions are contained in song lyrics, especially Nancy Ajram's songs, based on David Krech's emotion classification theory. The research method used in this research is a qualitative descriptive research method in which the results of the analysis are described and qualified based on the existing theory. used is David Krech's emotion classification theory. The results of this research are, of the four classifications of emotions proposed by David Krech, not all classifications of emotions are found in the lyrics of Nancy Ajram's songs, Nancy Ajram's songs are suitable as a medium for expressing emotions, of course by knowing the contents of the song first.